Exchange Rate Regimes in the Asia-Pacific Region and the Global Financial Crisis - Warwick J. McKibbin; Waranya Pim Chanthapun (Asian Development Bank (ADB), 2009)
Rising economic integration in Asia and periodic volatility in global and national financial markets raise the issue of the optimal degree and form of monetary cooperation among Asian economies. There is a large literature on the benefits and costs of monetary cooperation, however, less can be found with a specific focus on Asia. A number of studies have explored whether Asia might form an optimal currency area, although these have focused on the nature of shocks, in particular business cycle correlations, as well as the extent of trade linkages among economies. Less has been done on the impact of portfolio shifts and financial shocks, and how these shocks impact on financial cooperation. > This paper has two goals. The first is to explore the impacts of the current global financial crisis on Asian economies under existing monetary and exchange rate arrangements. The second is to explore how alternative forms of cooperation and exchange rate regimes might change the economic outcomes in Asia. In particular, the paper explores the impact of current regimes compared to one of three hypothetical regimes: (i) all countries peg to the US dollar, (ii) all Asian economies are in an Asian Currency Union with an Asian Central Bank setting policy, or (iii) floating exchange rates with each central bank in Asia independently choosing optimal time-consistent, close-loop policy rules to target a loss function consisting of deviation in inflation and output growth from desired levels.
hdl:11540/1826
Keywords: E27; E42; E44; E52; E58; F41; F42; 330; Monetary cooperation; exchange rates; financial crisis